2010
DOI: 10.1177/0218492310375855
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Medical Treatment of Acute Type A Intramural Hematoma

Abstract: A retrospective study was performed in 30 patients who were treated for type A intramural hematoma from 1999 to 2008, of whom 24 were initially treated without surgical intervention. These 24 patients were followed up for 3.3 +/- 3.5 years (range, 0 days to 10.0 years). Four hospital deaths occurred (hospital mortality, 16.7%), there were 2 late deaths, and 2 other patients needed an operation during the follow-up period. The event-free survival rate (freedom from death or surgery) at 5 years was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…IMH has historically been differentiated from aortic dissection in that the intimal layer remains intact in IMH, and IMH is believed to originate from ruptured vasa vasorum in the aortic media. However, there are increasing reports of small intimomedial tears not apparent at preoperative imaging that were found at surgery in a variable percentage of IMH cases, prompting discussion about the importance of the "microintimal tear" and whether it is the true inciting event rather than vasa vasorum rupture (2,3,5). An alternative explanation is that these cases labeled IMH were actually cases of thrombosed or noncommunicating aortic dissection that were erroneously diagnosed as IMH at imaging because of lack of a visible intimomedial tear.…”
Section: Imh: Pathophysiology and Controversiesmentioning
confidence: 99%
See 3 more Smart Citations
“…IMH has historically been differentiated from aortic dissection in that the intimal layer remains intact in IMH, and IMH is believed to originate from ruptured vasa vasorum in the aortic media. However, there are increasing reports of small intimomedial tears not apparent at preoperative imaging that were found at surgery in a variable percentage of IMH cases, prompting discussion about the importance of the "microintimal tear" and whether it is the true inciting event rather than vasa vasorum rupture (2,3,5). An alternative explanation is that these cases labeled IMH were actually cases of thrombosed or noncommunicating aortic dissection that were erroneously diagnosed as IMH at imaging because of lack of a visible intimomedial tear.…”
Section: Imh: Pathophysiology and Controversiesmentioning
confidence: 99%
“…The improved spatial resolution of thin-section multidetector CT allows prospective identification of some intimomedial tears in patients with IMH. Investigations of type A IMH have identified intimomedial defects in 58%-73% of patients, although one study included patients with coexistent type B aortic dissection, and not all studies differentiated small intimomedial defects from a larger ulcerlike projection or PAU (2,3,5). It is possible that even more of these patients may have had intimomedial defects that were not discovered surgically because there was not enough clinical suspicion for distal intimomedial defects to prompt further exploration at surgery, particularly in cases of IMH isolated to the ascending aorta (2).…”
Section: Imh: Pathophysiology and Controversiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of death is, in fact, increased in patients who develop complications 1. In a study published in 2010, including 30 patients with type A IMH, Sawaki et al 10 demonstrated that the outcome of medical treatment for this condition was acceptable during both the early and the late periods, but patients with a relatively large aortic diameter (≥48 mm) or an intimal defect in the ascending aorta have a high probability of adverse outcome and must be considered for surgery. In the Song's study the initial aorta diameter >55 mm and haematoma thickness >16 mm were independent predictors of complications 9.…”
Section: Discussionmentioning
confidence: 99%